Cigarette Smoke Detection And Cleaner Based On Internet Of Things (IoT) Using Arduino Microcontroller And MQ-2 Sensor - Yuda Irawan; Andre Wahyu Novrianto; Hafizh Sallam (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2021)
The detector and neutralize cigarette smoke in the STMIK Hang Tuah Pekanbaru there is no. To simplify detector and neutralize cigarette smoke in the campus area made a system detector and neutralize cigarette smoke Arduino Uno microcontroller based using an notification iot. The whole tool is divided into several parts, consisting of sensor mq-2, module ESP8266-01S, module LCD, mikrokontroller arduino uno, buzzer, and DC FAN. This tool works when module ESP8266-01S looking for the nearest internet network and sensor mq-2 detect cigarette smoke, from module ESP8266-01S and sensor mq-2 then to Arduino Uno microcontroller to process, from Arduino Uno microcontroller then Turn on buzzer as a warning alarm and Turn on DC FAN as a fan to neutralize cigarette smoke which then transfers data through module ESP8266-01S to the website and give notification the room detected cigarette smoke to the smartphone head of equipment and officers. The results showed that the smoke content was more than 300 detected as cigarette smoke, because it has been to test the system to several prototypes and 2hen there is no cigarette smoke was value is less than 300.